2018
DOI: 10.4067/s0370-41062018000200261
|View full text |Cite
|
Sign up to set email alerts
|

Avances en el conocimiento de las proteínas de la leche materna

Abstract: Recibido el 25 de abril de 2017; aceptado el 12 de octubre de 2017 Palabras clave: Leche materna; enzimas; péptidos; tripsina; plasmina ResumenLa glándula mamaria y la leche materna son el resultado de millones de años de una evolución que llevó a una composición óptima para el crecimiento y desarrollo de recién nacidos y lactantes; la leche materna favorece el crecimiento, la adaptación y la supervivencia de su organismo y de sus órganos inmaduros. Análisis recientes han demostrado en ella la presencia de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Molecular attributes of stratification and compartmentalization are largely found in HM containing mucins, large amounts of AMPs and IgA as well as diverse immune cell types, which can evolve across lactation and respond to mother or infant infection (Schroten, 2001; Hassiotou et al, 2013b; Trend et al, 2015a; Donovan, 2019). This was illustrated by several biochemical and proteomic studies, as well as the more recent flow cytometry-based cell analysis of fresh HM samples across the world (Patton, 2001; Ballard and Morrow, 2013; Hassiotou et al, 2013a; Wada and Lonnerdal, 2014; Brunser, 2018). Hence, microbiota found in the resting mammary gland or HM might impact molecular and cellular processes behind stratification and compartmentalization resulting in a mucosal-like immune system organization in mammary tissue.…”
Section: Beyond Nutrition: Evolutionary Origin Of the Mammary Gland Amentioning
confidence: 97%
“…Molecular attributes of stratification and compartmentalization are largely found in HM containing mucins, large amounts of AMPs and IgA as well as diverse immune cell types, which can evolve across lactation and respond to mother or infant infection (Schroten, 2001; Hassiotou et al, 2013b; Trend et al, 2015a; Donovan, 2019). This was illustrated by several biochemical and proteomic studies, as well as the more recent flow cytometry-based cell analysis of fresh HM samples across the world (Patton, 2001; Ballard and Morrow, 2013; Hassiotou et al, 2013a; Wada and Lonnerdal, 2014; Brunser, 2018). Hence, microbiota found in the resting mammary gland or HM might impact molecular and cellular processes behind stratification and compartmentalization resulting in a mucosal-like immune system organization in mammary tissue.…”
Section: Beyond Nutrition: Evolutionary Origin Of the Mammary Gland Amentioning
confidence: 97%
“…Breast milk results from an evolutionary process estimated to take more than 200 million years. It has been shown that the primitive mammary gland arose in terrestrial ancestors of mammals, and it has been speculated that the secretion of these primitive glands was gaining in complexity (15). The mammary glands of mammals derive from the ectoderm and are in the so-called "milk line", on the anterior aspect of the thorax or abdomen.…”
Section: Historical Background On Breastfeeding and Human Milk Banksmentioning
confidence: 99%
“…It has multiple components: proteins, carbohydrates, fats, cells, water, vitamins, among others (Fig. 5) (5,(11)(12)(13)15,21,23,25,(27)(28)(29)(30).…”
Section: Composition Of Breast Milkmentioning
confidence: 99%
See 2 more Smart Citations